Pengembangan Bahan Ajar Menulis Teks Eksplanasi Berbasis Kontekstual dengan Menggunakan Animasi - Munir, Misbahul; Boeriswati, Endry; Yarmi, Gusti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Writing skills are one of the most difficult skills to do. A change is needed to stimulate students to be interested in writing. Animation is expected to be a solution in making it easier for students to think.This study aims to 1) determine the needs of students for teaching material products to write contextual-based explanations using animation by utilizing web animaker 2) design teaching material models for writing contextual-based explanations using web animaker animations 3) implementing contextual-based explanatory writing teaching materials using web animaker animations 4) analyzing the results of expert validation and feasibility tests for teaching materials writing contextual-based explanations using web animaker animations. This method use R&D. This research and development refers to the ADDIE development model. The result can improved students. The feasibility test results of teaching materials received an average of 3.8 with a percentage of 95% in the â€œVery Decentâ€ category and an average score from media experts of 3.75 or a percentage of 94% in the â€œVery Decentâ€ category. The results of Indonesian teacher feedback at MA Annajah Petukangan South Jakarta obtained an average of 3.6 with a percentage of 90% thus it can be categorized as â€œVery Feasibleâ€. Small-scale trial 38 students obtained an average of 3.89 and a percentage of 97.4%. Thus, based on a likert scale of 3.21 to 4, it can be categorized as â€œVery Decentâ€.